From seduction to registration: case studies of women in the sex industry - Worley, Robert (Criminal justice studies, 2022)
In this exploratory study, we conducted in-depth interviews with three females who were employed in the sex industry which ultimately led to their arrest, conviction, and registration as a sex offender. In all three cases, the interviewees were co-offenders who committed a sex crime at the behest of a dominant male partner whom they met through the adult entertainment industry. This study suggests that women who are employed in the sex industry may be at a heightened risk of becoming entangled in the criminal justice system and being labeled as sex offenders. Further research is warranted in this area.